Faire des économies avec la remise en logement ? Une comparaison des coûts avec ceux du sans-chez-soirisme - Justine Carlier; Magali Verdonck (Brussels Studies, 2024)
The implementation of the “Housing First” project in several countries, such as France and Canada, has shown that allowing the homeless to obtain housing in order to reintegrate them into society can sometimes cost the state less than leaving them on the streets. Despite a political will in Belgium and Europe to prevent and end homelessness, no study has been carried out in French-speaking Belgium regarding its cost to society, making it impossible to assess the policies in place and any necessary changes. The aim of the study summarised in this article was to assess the cost of homelessness in the Brussels-Capital Region, taking into account both direct and indirect costs, which were then compared to the costs associated with rehousing the homeless.